The effect of land costs on the economic and sustainability performance of solar photovoltaics in China - Shi Chen; Xi Lu; Jiming Hao; Edgar Virgüez; Ken Caldeira; Steven J. Davis (Proceedings of the National Academy of Sciences, 2026)
Scaling up solar photovoltaics (PV) is essential for global decarbonization, particularly in China—the world’s largest greenhouse gas (GHG) emitter. Despite leading in PV installations, China has yet to widely adopt the more efficient tracking technologies for capturing solar radiation (12% adoption rate), in stark contrast to the United States (90%). To examine the rationale behind this divergence and its consequences, we develop a spatially explicit, integrated model to evaluate and compare tracking and fixed-tilt systems in China—comparing power generation, land use, cost, sustainability, and policy resilience. We find that although single-axis tracking provides electricity gains and appears technically more cost-effective, rising land prices in China could offset its benefits. Land costs increase the levelized cost of electricity by 20% for tracking systems, compared to 8% for fixed-tilt, making the latter cheaper in real-world conditions. Consequently, land-efficient fixed-tilt systems are favored, despite requiring 18 to 26% more panels for the same output—intensifying material demands. Under a 6 PWh target in 2060, current land policies would drive 59% of electricity toward fixed-tilt. Reducing soft land costs could increase the adoption of tracking systems to 63% and reduce installed capacity by up to 8% (219 GW) under the same electricity output, compared with an increasing costs scenario, but would expand land use by 35% or 12.9 thousand km 2 . Our findings underscore how land economics and policy shape renewable technology deployment. They highlight critical trade-offs between energy yield, land use, and material demand, offering insights for designing more balanced and resilient decarbonization strategies.